Leadership and Management: Case Studies in Training in Higher Education in Africa - Wildschut, Lauren; Mouton, J. (Johann); Project Muse; Project Muse. (Project Muse, 2015)
There has been a resurgence of interest in training programmes for higher education leaders and management (HELM) at African universities in recent times. Although there have been a few cases of evaluation studies of such programmes in Africa, a more systematic review of the lessons learnt through these programmes has not been done. This book aims to document and reflect on the learnings from intervention programmes at three African higher education councils. It is clear that university leaders face many leadership and management challenges. This is the starting point of the book.
Preface -- Introduction : origins of the project -- part one. Issues and challenges -- 1. A review of the scholarship on helm training in Africa -- 2. The context of helm training in Africa -- part two. Country case studies -- 3. Tanzania -- 4. Uganda -- 5. Ghana -- part three. Monitoring and evaluation -- 6. An evaluation framework -- 7. Knowledge exchange -- Appendix A. AAU research paper series -- Appendix B. Questionnaire for online survey -- Appendix C. Sample training framework -- Appendix D. Checklist for a cohesive training programme -- Appendix E. Sample checklist for reviewing training materials.
"Supported by Carnegie Corporation of New York."
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Universities and colleges -- Africa -- Aministration; Educational leadership -- Africa -- Case studies; College administrators -- Training of -- Africa -- Case studies; Electronic books; Electronic books